1998
DOI: 10.1111/0952-1895.581998058
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Administrative Reform and Governance: An Examination of the Political Nexus Triads in Three Asian Countries

Abstract: When addressing administrative reform, many scholars have referred to the fact that governments confront multiple internal challenges such as fiscal stress, distrust of bureaucracy, and higher demands for public services (Peters and Savoie 1995). Externally, governments become more sensitive to global issues and tend to be more influenced by international environments (Garcia‐Zamor and Khator 1994). Faced with internal and external challenges, governments seek new paradigms for governance (Ingraham and Romzek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 25 publications
(40 reference statements)
1
35
0
1
Order By: Relevance
“…A second orientation of the demand-side explanation is related to what may be referred to as the "political nexus triad" (PNT), in which politicians, bureaucrats and citizens negotiate their political interests regarding the function and structure of government (Moon & Ingraham, 1998). The dominant interests in the PNT emerge to shape the structure and function of government, which may be to the exclusion of others' interests.…”
Section: E-governancementioning
confidence: 99%
“…A second orientation of the demand-side explanation is related to what may be referred to as the "political nexus triad" (PNT), in which politicians, bureaucrats and citizens negotiate their political interests regarding the function and structure of government (Moon & Ingraham, 1998). The dominant interests in the PNT emerge to shape the structure and function of government, which may be to the exclusion of others' interests.…”
Section: E-governancementioning
confidence: 99%
“…We utilised the Political Nexus Triad scheme (Moon & Ingraham, 1998) to form the analytical categories: politicians, bureaucrats and civil society. In order to categorise a policy entrepreneur as a politician he/she would have to belong to the municipal executive, municipal legislature or politically appointed top-management.…”
Section: Operationalisation Of the Concepts Of Entrepreneurship Decementioning
confidence: 99%
“…Policymaking, as a study of three Asian countries concluded, is often the product of interaction between politicians, bureaucracy and civil society. These forces may be seen then to form a 'Political Nexus Triad' (Moon and Ingraham, 1998). However, in the Punjab it was a 'politico-bureaucratic nexus'.…”
Section: Roles and Interests Of Different Groups In The Policy Processesmentioning
confidence: 99%